Cannabis as a cause of death: A review. (May 2019) - Drummer, Olaf H.; Gerostamoulos, Dimitri; Woodford, Noel W.
Highlights: Smoking cannabis has been associated with acute myocardial infarction. Some deaths have been attributed to smoked cannabis. Thrombus formation and stroke has been associated with use of cannabis. Acute use of cannabis should be considered as contributory to death in some cases. Abstract: Synthetic cannabinoids have caused a large number of emergency presentations to hospitals for adverse cardiovascular events including numerous deaths, particularly for the more potent analogs acting on the CB1 receptor. While smoked cannabis use is often associated with significant changes in heart rate and cardiac output, amongst other physiological changes, it has been rarely considered in the forensic literature as a significant contributory or causal factor in sudden unexpected death. A review of case reports of admissions to hospitals for cardiovascular events was undertaken together with a review of epidemiological studies, and case reports of sudden death attributed, at least in part, to use of this drug. These publications show that use of cannabis is not without its risks of occasional serious medical emergencies and sudden death, with reports of at least 35 persons presenting with significant cardiovascular emergencies who had recently smoked a cannabis preparation. At least 13 deaths from a cardiovascular mechanism have been reported from use of this drug which is very likely to be an under-estimate of the true incidence of its contribution to sudden death. In addition, many cases of stroke and vascular arteritis have also been reported with the latter often involving a limb amputation. While it is a drug with widespread usage among the community with relatively few deaths when faced with a circumstance of very recent use (within a few hours), a positive blood concentration of THC and a possible cardiac-related or cerebrovascular cause of death this drug should be considered, at least, a contributory cause of death in cases of sudden or unexpected death.